Signifikasi Peradilan Tata Usaha Negara Di Wilayah Provinsi Maluku Utara - Maryadi (Universitas Islam Indonesia, 2022)
The establishment of the State Administrative Court as the last court formed in accordance with the constitutional mandate contained in Article 24 of the 1945 State Constitution, was manifested into Law Number 5 of 1986 on the State Administrative Court. This study examines the significance of the State Administrative Court in North Maluku Province. This research is juridical-normative in nature and is presented in a descriptive-qualitative manner. The results of the study concluded that the existence of the State Administrative Court in the North Maluku region to response to legal disputes brought before the State Administrative Court area is increasing. The presence of the State Administrative Court is a Constitutional order.Key Words: Establishment; state administrative court; legal disputes Abstrak Lahirnya Peradilan Tata Usaha Negara sebagai peradilan yang terakhir dibentuk sesuai amanah konstitusi tertuang dalam Pasal 24 Undang – Undang Dasar Negara 1945, di wujudkan menjadi Undang – Undang Nomor 5 Tahun 1986 Peradilan Tata Usaha Negara. Penelitian ini mengkaji, bagaimana signifikasi Peradilan Tata Usaha Negara di Provinsi Maluku Utara. Penelitian ini bersifat yuridis – normatif dan disajikan secara dekriptif – kualitatif. Hasil kajian menyimpulkan bahwa keberadaan Peradilan Tata Usaha Negara di wilayah Maluku Utara untuk menjawab problem sengketa hukum di wilayah Peradilan Tata Usaha Negara semakin meningkat. Kehadiran Peradilan Tata Usaha Negara merupakan perintah Konstitusi.Kata- kata Kunci: Pembentukan; peradilan tata usaha negara; sengketa hukum